2022
DOI: 10.1007/s00376-022-1247-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Regional Combustion Efficiency using ΔXCO: ΔXCO2 Observed by a Portable Fourier-Transform Spectrometer at an Urban Site in Beijing

Abstract: Measurements of column-averaged dry-air mole fractions of carbon dioxide and carbon monoxide, CO 2 (XCO 2 ) and CO (XCO), were performed throughout 2019 at an urban site in Beijing using a compact Fourier Transform Spectrometer (FTS) EM27/SUN. This data set is used to assess the characteristics of combustion-related CO 2 emissions of urban Beijing by analyzing the correlated daily anomalies of XCO and XCO 2 (e.g., ΔXCO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 74 publications
1
8
0
Order By: Relevance
“…The measurement conducted in the Netherlands by Super et al (2017) found the mean ratios in different cities varying from 2.0-3.9 ppb ppm −1 in 2014-2015, and a ratio of 3.01-6.80 ppb ppm −1 in France from 2013 to 2014 was measured by Ammoura et al (2016). Moreover, the ∆CO/∆CO 2 ratio is in the range of 10.5-60.2 for other cities in China (Liu et al 2018, Xia et al 2020, Che et al 2022, Li et al 2022. Therefore, there is still a long way to go for China to improve its combustion efficiency.…”
Section: Observed ∆Co/∆co 2 Ratiosmentioning
confidence: 96%
See 1 more Smart Citation
“…The measurement conducted in the Netherlands by Super et al (2017) found the mean ratios in different cities varying from 2.0-3.9 ppb ppm −1 in 2014-2015, and a ratio of 3.01-6.80 ppb ppm −1 in France from 2013 to 2014 was measured by Ammoura et al (2016). Moreover, the ∆CO/∆CO 2 ratio is in the range of 10.5-60.2 for other cities in China (Liu et al 2018, Xia et al 2020, Che et al 2022, Li et al 2022. Therefore, there is still a long way to go for China to improve its combustion efficiency.…”
Section: Observed ∆Co/∆co 2 Ratiosmentioning
confidence: 96%
“…Studies of combustion efficiency using the observed atmospheric ∆CO/∆CO 2 ratio, especially long-term ones, are even more limited in China. The majority of ∆CO/∆CO 2 ratio studies are concentrated in the areas around Beijing (Han et al 2009, Wang et al 2010, Turnbull et al 2011b, Liu et al 2018, Che et al 2022, Li et al 2022. Our study area, the Yangtze River Delta (YRD) region, covers the alluvial plains surrounding the Yangtze River estuary with an area of around 350 000 square kilometers and is home to over 240 million people.…”
Section: Introductionmentioning
confidence: 99%
“…According to the MEIC inventory 45 The neglect of human respiration can cause underestimations of emission ratios (ER, e.g., ΔCO/ΔCO 2 and ΔNO x /ΔCO 2 ) derived from direct measurements since the observed CO 2 is misattributed to fossil fuel emissions. A lot of open-air observational studies impute the higher inventoryderived ER to overestimation by emission inventories, 29,30,47 while excellent agreements between local inventory CO/CO 2 ratio for the traffic sector and the observed ΔCO/ΔCO 2 ratio are obtained in a tunnel study, in which CO 2 and pollutants (CO, NO x , and VOCs) measurements were performed in a road tunnel in Paris, 48 which is close to the origin of the air mass. It is worth stressing that the neglect of human respiration may not necessarily indicate that ERs from previous observations are incorrect, and bias may also occur in ERs derived from inventory.…”
Section: Urbanmentioning
confidence: 97%
“…A similar ground-based highresolution FTIR observatory at Xianghe has also passed the TCCON quality inspection and joined the TCCON network in 2021 (Yang et al, 2020c). Furthermore, a few affiliations started to operate the portable EM27/SUN FTIR spectrometers and became COCCON members in recent three years (Frey et al, 2019;Liu et al, 2022;Che et al, 2022). 4.…”
Section: Advances In Ghgs Monitoring In Chinamentioning
confidence: 99%